ago
0 like 0 dislike
0 like 0 dislike
ago
0 like 0 dislike
0 like 0 dislike
One way:

(2^(n) + (-2)^(n))/2^(n) =

2^(n)/2^(n) + (-2)^(n)/2^(n) =

(2/2)^(n) + (-2/2)^(n) =

1^(n) + (-1)^(n) =

1 + (-1)^(n)
ago
0 like 0 dislike
0 like 0 dislike
Looking at it the easiest way would be to go

2^(n)+(-2)^(n)/2

(2/2)(1^(n)+(-1)^(n))/1

2/2=1 and m/1=m and 1^n =1

Therefore
1+(-1)^n
ago
0 like 0 dislike
0 like 0 dislike
= 2^n / 2^n + (-2)^n / 2^n

>!= 1 + (-2/2)^n!<
ago

No related questions found

33.4k questions

135k answers

0 comments

33.7k users

OhhAskMe is a math solving hub where high school and university students ask and answer loads of math questions, discuss the latest in math, and share their knowledge. It’s 100% free!